Obtenção de anticorpos monoclonais murinos contra antígenos de Staphylococcus aureus resistentes à meticilina por imunização subtrativa - Simões, Ana Claudia [UNESP] (2015)
The MRSA infections are considered a public health problem, with a high mortality rate. Thus, with the wide spread of MRSA it's necessary to embrace monitoring programs to evaluate the sensitivity profile of the isolates, as well as to stimulate technological development aiming faster and more reliable methods to anticipate the choice of the most appropriate therapy by proposing methods of prevention and vaccines to advance the control of hospital infections. Therefore, this study aims the characterization of anti-MRSA monoclonal antibodies obtained by classical immunization protocols and the obtaining of other antibodies with the subtractive immunization method. We used 10 Balb/C mice that received as tolerogen proteins of strains of E. coli and MSSA associated with 100mg/kg/d of cyclophosphamide (Cy) in D1, D2, D3, D 15, D16 and D17. On D+31, 38, 45 and 54 we made injections of 50 μg of the MRSA strain protein, previously genotyped and with confirmed presence of mec A. We prepared antigenic extracts by 3 different methods: boiling, death at ambient temperature followed by 0.22 μm filtration and death at ambient temperature and exposure to ultrasonic wash.The boiling method resulted on average 5.31mg/mL, whereas the technique of death at ambient temperature, filtered or exposed to ultrasonic wash culminated on average in a protein concentration two times higher, indicating the existence of heat labile proteins.We identified a mortality rate of 30% in the animals, which was probably associated with the use of Cy. We performed seven cellular fusions with the construction of 4.402 hybrids with a fusion efficiency rate of 2.42 times smaller than that obtained in protocols of classical immunization.We selected two hybridomas for cloning by the limiting dilution method, whose immunochemical characterization identifies bands of 30 and 50 kDa. The proteomic analysis of protein bands that was recognized by the two clones confirm that the ...